Managing Crisis Communications in a Volatile, Uncertain, Complex, and Ambiguous World - Suteetorntorn, Bussaba (Executive Journal, 2020)
The world is facing a new normal situation of VUCA which is an acronym of volatility (V), uncertainty (U), complexity (C), and ambiguity (A). First, volatility refers to rapid changes and unpredictability situations; uncertainty (U) is a state of non-clarity, lack of information, and incapability of using existing knowledge or experience to make sense of the condition; complexity (C) represents the status where numerous difficulties exist and are challenging to understand and find solutions; and ambiguity (A) denotes the condition when ambiguous causes are involving in which the situations are challenging to verify. The current situation suggests that the management practices applied in the past may not be used successfully in the present. Moreover, some organizations are unprepared or unable to respond effectively in accordance to the changing situations, and may consequently face a new crisis. In crisis management, one of the vital components is an effective communication among the organizations’ staffs and with their stakeholders. This article aims to build an understanding of the situation in the age of volatility, uncertainty, complexity, and ambiguity, and propose some crisis communication principles for executives to deal with the crisis.